Pengukuran Kinerja Mesin Perusahaan Menggunakan Overall Equipment Effectiveness Dan Usulan Perbaikan Menggunakan Diagram Sebab Akibat (Fish-Bone) Pada CV. Jati Makmur Pasuruan - Fredo Karismawan; Puspandam Katias (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2015)
This study aims to to know costs inflicted of a system of preventive maintenance and maintenance of the breakdown and its effect on downtime .The research was done in the lumber cv .Jati prosper with the qualitative study approach uses the descriptive .  Procedures data collection in penellitian it has several stages of , namely the preliminary survey , theoretical survey , and field study .       The result from research found that among januari until december 2010 OEE range 65,093% -81,175%.after research found that two factors majority affect OEE value in CV.Jati Makmur two factors is reduce speed losses and setup and adjustment losses with proportion 45,83% and 40,88%.